Biomechanical Properties of the Sarcolemma and Costameres of Skeletal Muscle Lacking Desmin - Garcia-Pelagio, Karla P.; Bloch, Robert J. (Frontiers in Physiology, 2021)
Intermediate filaments (IFs), composed primarily by desmin and keratins, link the myofibrils to each other, to intracellular organelles, and to the sarcolemma. There they may play an important role in transfer of contractile force from the Z-disks and M-lines of neighboring myofibrils to costameres at the membrane, across the membrane to the extracellular matrix, and ultimately to the tendon (“lateral force transmission”). We measured the elasticity of the sarcolemma and the connections it makes at costameres with the underlying contractile apparatus of individual fast twitch muscle fibers of desmin-null mice. By positioning a suction pipet to the surface of the sarcolemma and applying increasing pressure, we determined the pressure at which the sarcolemma separated from nearby sarcomeres, Pseparation, and the pressure at which the isolated sarcolemma burst, Pbursting. We also examined the time required for the intact sarcolemma-costamere-sarcomere complex to reach equilibrium at lower pressures. All measurements showed the desmin-null fibers to have slower equilibrium times and lower Pseparation and Pbursting than controls, suggesting that the sarcolemma and its costameric links to nearby contractile structures were weaker in the absence of desmin. Comparisons to earlier values determined for muscles lacking dystrophin or synemin suggest that the desmin-null phenotype is more stable than the former and less stable than the latter. Our results are consistent with the moderate myopathy seen in desmin-null muscles and support the idea that desmin contributes significantly to sarcolemmal stability and lateral force transmission.